Pengaruh Kualitas Pelayanan dan Fasilitas Digital Terhadap Minat Membayar Zakat Profesi melalui BAZNAS Kabupaten Tegal dengan Kepercayaan Sebagai Variabel Intervening (Studi Kasus Muzakki Potensial Di Kabupaten Tegal): Studi Kasus Muzakki Potensial di Kabupaten Tegal - Salsabila Maryunia; Hendri Sucipto; Andi Yulianto (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The focus of this study is to provide an understanding of how BAZNAS Tegal Regency provides services to muzakki, the use of digital technology by BAZNAS Tegal Regency in influencing the views and beliefs of the community, and its influence on the level of interest of muzakki. The population is muzakki who are recorded as paying professional zakat through BAZNAS Tegal Regency. The research method uses quantitative. Data collection techniques with questionnaires. Data analysis using SmartPLS. The number of samples that will be used to represent the population is 100 respondents. The results of this study prove that service quality does not have a significant effect on interest in paying professional zakat, digital facilities have a significant effect on interest in paying professional zakat. Then the quality of service has a significant effect on the trust of muzakki, digital facilities have a significant effect on the trust of muzakki. Trust has a significant effect on interest in paying professional zakat. Service quality has a significant effect on interest in paying professional zakat at BAZNAS Tegal Regency mediated by trust. Digital facilities have a significant effect on interest in paying professional zakat trust. The research findings are expected to provide valuable insights for BAZNAS Tegal Regency in improving its services and facilities to encourage zakat collection and strengthen the trust and involvement of muzakki.